2012
DOI: 10.1111/j.1743-498x.2012.00557.x
|View full text |Cite
|
Sign up to set email alerts
|

Data protection training improves data handling

Abstract: With the expansion of patient data collection and storage, it is important for doctors to maintain an awareness of how to handle such data. DPT is not currently common practice. Our study suggests positive benefits from DPT, and we suggest it could improve the safety with which patient data is handled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The results of the second phase after the intervention in the present study showed that the users observed various aspects related to the security of computer systems and the confidentiality of information more than before such as not leaving the computer systems switched on, locking the system if not being used, using a password for log-in, and autolock of the systems if not in use after a certain time. However, users should be constantly trained on computer skills, because improving their computer knowledge can lead to observing computer systems' security and information confidentiality more often 3,4,6,18,20 . In addition to the above, the access of unauthorized users to computer systems left switched on and unused can be prevented by using technologies of log-in with biometric information such as fingerprints and building them on the mouse or keyboard of computers 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the second phase after the intervention in the present study showed that the users observed various aspects related to the security of computer systems and the confidentiality of information more than before such as not leaving the computer systems switched on, locking the system if not being used, using a password for log-in, and autolock of the systems if not in use after a certain time. However, users should be constantly trained on computer skills, because improving their computer knowledge can lead to observing computer systems' security and information confidentiality more often 3,4,6,18,20 . In addition to the above, the access of unauthorized users to computer systems left switched on and unused can be prevented by using technologies of log-in with biometric information such as fingerprints and building them on the mouse or keyboard of computers 19 …”
Section: Discussionmentioning
confidence: 99%
“…However, users should be constantly trained on computer skills, because improving their computer knowledge can lead to observing computer systems' security and information confidentiality more often. 3,4,6,18,20 In addition to the above, the access of unauthorized users to computer systems left switched on and unused can be prevented by using technologies of log-in with biometric information such as fingerprints and building them on the mouse or keyboard of computers. 19 According to the results of the first and second phases of the present study, there was no change in using users' own personal passwords.…”
Section: Comparisons With Existing Literaturementioning
confidence: 99%